Evaluated Potential of Mica Waste to Release Sufficient Potassium to Support the Growth of Plants in Acidic Tea-Growing Soil in Northeast India. Issue 10 (31st May 2019) - Pramanik, Prabhat; Kalita, Chayanika
ABSTRACT: Tea ( Camellia sinensis L.) is a nutrient-demanding perennial crop and cultivated in typically acidic soil under sub-tropic humid condition. A large amount of fertilizers, especially urea and muriate of potash (MoP), are applied in the soil to sustain tea productivity. However, high potassium (K)-loss from soil under humid conditions suggests the requirement of an alternative K source for supplementing K in the soil during tea cultivation. The objective was to evaluate the possibility of using K-containing minerals, namely, potassium feldspar (K-spar) and mica waste (WM), as alternative K-source for supplementing K in the soil. In this study, application of WM at the recommended dose increased exchangeable K content in soil compared to control (received no K input); however, the value was lower than that of MoP treatment. The WM-treated plants had better growth and higher K uptake than plants with the MoP treatment. Application of WM at half of the recommended dose increased K content in the soil above no K-treated soil and recorded comparable growth and K accumulation by plants as MoP. MW could be used as K amendment in acidic soil, especially during tea cultivation.